Drevesa z možnostjo večnamenske rabe, s poudarkom na travniških sadovnjakih - Ferreira, Andreja (Gozdarski vestnik, 2013)
Multipurpose trees are an agroforestry subsystem, where fruit and other trees are randomly or systematically planted in cropland or pasture for the purpose of providing fruit, fuelwood, fodder and timber, among other services. In Western, Central and Eastern Europe one of the most recognizable and most widespread traditional forms of multipurpose tree are fruit-tree meadow orchards. They are also one of the most widespread agricultural land uses in Slovenia that gives a unique mark to our landscape. The fruit-tree meadow orchards in Slovenia are defined as extensive plantations of tall-trunk fruit trees, with the minimum tree density of 50 trees/ha and the largest one not exceeding 200 trees/ha. Additionally to the fruit production, fruit-tree meadow orchards provide many other forms of services and are becoming an indispensable part of modern agricultural landscape. One of the most important measures for maintaining fruit-tree meadow orchards are grazing by livestock and mowing. Today, land use changes and lack of interest for their maintenance are the two main reasons threatening the existence of meadow orchards.
Keywords: drevesne vrste; večnamenska raba prostora; travniki; sadovnjaki; travniški sadovnjaki; kmetijsko-gozdarski sistemi; raba tal; Slovenia; Slovenija; Europe; Evropa